A beam formulation for large displacement analysis of composite frames with semi-rigid connections. (15th December 2015) - Turkalj, Goran; Lanc, Domagoj; Brnic, Josip; Pesic, Igor
Abstract: This paper presents a geometrically non-linear beam formulation for large displacement analysis of composite beam type structures with semi-rigid connections. Within the framework of updated Lagrangian incremental formulation and the nonlinear displacement field of thin-walled cross-sections, which accounts for restrained warping and the second-order displacement terms due to large rotations, the equilibrium equations of a straight beam element are firstly developed. Due to the nonlinear displacement field, the geometric potential of semitangential moment is obtained for both the internal torsion and bending moments, respectively. To account for the semi-rigid connection behaviour, a special transformation procedure is developed. The laminates are modelled on the basis of classical lamination theory. In order to illustrate the application of the proposed formulation, several numerical examples are presented.